3D Visualization Trends in Science Learning: Content Analysis - Nuri Vina Mawadah; Sabar Nurohman; Jaslin Ikhsan; Suyanta; Sri Rejeki (Jurnal Penelitian Pendidikan IPA, 2023)
In the current digital era, the development of science and technology is growing rapidly in the world of education. In learning the use of technology in the form of using smartphones and the internet which can be accessed by both teachers and students. Trends in learning by incorporating elements of technology in science learning. Science is a family of biology, physics, chemistry which has material characteristics that can be seen or observed by the senses and are not visible to the five senses and cannot be displayed in class. The natural aspect of science is quite broad because it relates to phenomena and natural phenomena, therefore 3D visualization is needed in learning so that abstract material can be more concrete in the meaning of learning. The purpose of this study is to analyze the content or content analysis of 20 articles related to 3D visualization in science learning. The results obtained are 3D visualization in learning used from elementary to high school levels. The 3D visualization is in the form of AR-based learning media and AR-based modules that affect the learning outcomes that teachers and students want to achieve. In making objects in the form of 3D visualization using several software, namely blender, unity, vuforia, AR, uniteAR.